2016
DOI: 10.18632/aging.101083
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autophagy activity is linked to elevated ER-stress and inflammation in aging adipose tissue

Abstract: Adipose tissue dysfunction in aging is associated with inflammation, metabolic syndrome and other diseases. We propose that impaired protein homeostasis due to compromised lysosomal degradation (micro-autophagy) might promote aberrant ER stress response and inflammation in aging adipose tissue. Using C57BL/6 mouse model, we demonstrate that adipose tissue-derived stromal vascular fraction (SVF) cells from old (18-20 months) mice have reduced expression of autophagy markers as compared to the younger (4-6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 52 publications
3
55
0
Order By: Relevance
“…On the other hand, impaired autophagic degradation can trigger ER stress. Ghosh et al [22] demonstrated that impaired autophagy in mouse adipose tissue from old animals Fig. 1 ER stress evokes inflammatory responses via the activation of three branches of ER stress sensors.…”
Section: Er Stress Stimulates Upr Signalingmentioning
confidence: 99%
“…On the other hand, impaired autophagic degradation can trigger ER stress. Ghosh et al [22] demonstrated that impaired autophagy in mouse adipose tissue from old animals Fig. 1 ER stress evokes inflammatory responses via the activation of three branches of ER stress sensors.…”
Section: Er Stress Stimulates Upr Signalingmentioning
confidence: 99%
“…Finally, a reduced autophagic rate has been demonstrated to contribute to inflammation and endoplasmic reticulum stress in adipose tissue of aged mice, which suggests a role for autophagy in the metabolic derangements in aging adipose tissue (126). In fact, compromised autophagy activity in preadipocytes from aged mice was correlated with the enhanced release of proinflammatory cytokines, IL-6 and monocyte chemotactic protein-1 (126).…”
Section: Autophagy In Adipose Tissuementioning
confidence: 99%
“…For example, a study examining autophagy and ER stress in aging adipose tissue-derived stromal vascular fraction cells (SVF) demonstrates that aged SVF cells exhibit decreased autophagy and increased ER-stress [74]. Furthermore, the loss of autophagy in mouse colorectal tumors via genetic inhibition of ATG5 or treatment with the lysosomal inhibitor chloroquine lead to elevated ER stress as well as increased CHOP and BiP expression [75].…”
Section: Er Stress and Mtor Signaling During Detachment-induced Autopmentioning
confidence: 99%